2018
DOI: 10.1177/1093526618819605
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Month-Old Infant Presenting With Signs of Precocious Puberty Secondary to a Sclerosing Stromal Tumor of the Ovary in the Absence of Hormonal Elevation

Abstract: Precocious puberty in an infant is an alarming and infrequent finding, making the differential diagnosis difficult for practitioners. Precocious puberty secondary to a sclerosing stromal tumor (SST) of the ovary is rare. We present a case of a child that began precocious puberty at 3 months of age including development of breast buds, pubic hair, growth spurt, and menarche 5 days prior to presenting to pediatric endocrinology at 10 months. She underwent right salpingo-oophorectomy which demonstrated a soft tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, in 1975, Damjanov et al reported the production of steroid hormones by SSTs [ 28 ]. Androgens and, less frequently, estrogens can lead to menstrual disturbances and signs of virilization or precocious puberty, as reported in several studies [ 8 , 12 , 21 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ]. Menstrual irregularities are very common in the first two years after menarche; therefore, this symptom may be underestimated in this population or simply attributed to a physiologically abnormal hormonal production.…”
Section: Discussionmentioning
confidence: 90%
“…However, in 1975, Damjanov et al reported the production of steroid hormones by SSTs [ 28 ]. Androgens and, less frequently, estrogens can lead to menstrual disturbances and signs of virilization or precocious puberty, as reported in several studies [ 8 , 12 , 21 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ]. Menstrual irregularities are very common in the first two years after menarche; therefore, this symptom may be underestimated in this population or simply attributed to a physiologically abnormal hormonal production.…”
Section: Discussionmentioning
confidence: 90%